Unveiling the Mathematical Tapestry: A Comparative Journey of Bharatvarsh and the World - Mishra, Ravindra (Patan Pragya, 2024)
The study aims to investigate the fundamental knowledge of the number system and its evolution, particularly in the context of Bharatvarsh (the Indian subcontinent) and its historical regions such as Awadh, Mithila, Pandecherri, Nepal, Gandaki desh, Bajhang, Tamsaling, Goa, Sindh, Delhi, and Gwalier.The research compares the mathematics developed in Bharatvarsh or South Asia with that of the European Union, drawing insights from the field of Jyotish Shastra (Astrology), where mathematics plays a crucial role. The findings highlight the unique aspects of mathematics in Bharatvarsh, revealing its distinct applications and development within the framework of Jyotish Shastra. The study emphasizes the importance of studying mathematics for undergraduate students and provides suggestions to facilitate their understanding of this subject. The research offers a fresh perspective on the evolution of the number system and of mathematical concepts, contrasting the approaches taken in Bharatvarsh and the European Union while underscoring the significance of Jyotish Shastra in shaping the mathematical traditions of South Asia.